Systematic Literature Review(SLR): The Influence of Intellectual Capital On Financial Performance in Developed and Developing Countries - Olivia Putri Zahrani; Hasni Yusrianti; Shelly Febriana Kartasari (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study examines the influence of intellectual capital on financial performance in developed and developing countries through a systematic literature review. The analysis included 35 peer-reviewed articles from 2019–2025 from databases such as ProQuest and ScienceDirect. Data extraction focused on the components of intellectual capital—human, structural, and relational—and their impact on financial metrics, including Return on Assets. Bibliometric analysis, descriptive content analysis, and simple statistics were used to identify patterns and gaps. The results indicate a generally positive effect of intellectual capital, particularly consistent in developing countries. While in developed countries, the impact is more complex and context-dependent, with human capital sometimes having a negative impact due to high operating costs. Structural capital is the most stable contributor. Innovation and political connections strengthen the influence in developing countries, while governance and digital transformation play a role in developed countries. The conclusions emphasize the critical role of intellectual capital, which differs across economic contexts and the need for tailored management strategies. Future research recommends the development of adaptive models and longitudinal studies.